Representasi Budaya Tionghoa dalam Iklan Minuman Beralkohol pada Tahun 1931: Analisis Semiotika - Rizki Jefri Saputra; T. Kasa Rullah Adha; Muhammad Yusuf (Jurnal Ilmu Sosial dan Humaniora, 2026)
This study examines the representation of Chinese culture in alcoholic beverage advertisements from 1931 in the Dutch East Indies using Ferdinand de Saussure’s semiotic theory. Advertisements are not only understood as promotional media but can also be interpreted culturally; through an analysis of the relationship between signifiers and signifieds in both visual and linguistic elements, this research explores how these elements construct the identity of the Chinese community in such advertisements during the colonial period. The data were obtained from Chinese-language newspaper archives from 1931 housed in the National Library, which contain advertisements for alcoholic beverages, and were analyzed to uncover the constructed cultural meanings. The findings indicate that the representation of Chinese identity in these advertisements emphasizes perceived health benefits of the products, the use of specific symbolic imagery on labels, and the portrayal of modernity associated with purchasing power; thus, these advertisements function as a space for constructing Chinese cultural identity within the discourse of the colonial era.